Effects of mindfulness-based interventions on fatigue in cancer survivors: A systematic review and meta-analysis of randomized controlled trials. (April 2021) - Johns, Shelley A.; Tarver, Will L.; Secinti, Ekin; Mosher, Catherine E.; Stutz, Patrick V.; Carnahan, Jennifer L.; Talib, Tasneem L.; Shanahan, Mackenzie L.; Faidley, Micah T.; Kidwell, Kelley M.; Rand, Kevin L.
Graphical abstract: Highlights: Fatigue is a prevalent and disruptive symptom for many cancer survivors. Mindfulness-based interventions (MBIs) have been tested to reduce fatigue in cancer. Meta-analyses tested the efficacy of MBIs in cancer for fatigue and vigor/vitality. MBIs significantly improved fatigue and vigor/vitality compared to controls. Evidence grade was low due to risk of bias, heterogeneity, and publication bias. Abstract: This systematic review and meta-analysis was designed to determine the efficacy of mindfulness-based interventions (MBIs) in improving fatigue-related outcomes in adult cancer survivors. Randomized controlled trials (RCTs) were identified from PubMed, MEDLINE, PsycINFO, CINAHL, Web of Science, and EMBASE databases and reference lists of included studies. Separate random-effects meta-analyses were conducted for fatigue and vitality/vigor. Twenty-three studies reporting on 21 RCTs ( N = 2239) met inclusion criteria. MBIs significantly reduced fatigue compared to controls at post-intervention ( g = 0.60, 95 % CI [0.36, 0.83]) and first follow-up ( g = 0.42, 95 % CI [0.20, 0.64]). Likewise, MBIs significantly improved vitality/vigor at post-intervention ( g = 0.39, 95 % CI [0.25, 0.52]) and first follow-up ( g = 0.35, 95 % CI [0.03, 0.67]). The evidence grade was low due to risk of bias, substantial heterogeneity, and publication bias among studies. MBIs show promise in improving fatigue and vitality/vigor in cancer survivors. More rigorous trials are needed to address current gaps in the evidence base.